2019
DOI: 10.3390/su11174745
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pyramid of CSR for Corporate Image and Customer Loyalty: Focusing on the Moderating Role of the CSR Experience

Abstract: The current study aims to suggest a modified pyramid of corporate social responsibility (CSR) in the airline industry and find the moderating effects of consumer’s CSR experience (CSRE). Although previous studies proved the positive effects of CSR, there are surprisingly few research studies that incorporate Carroll’s fundamental CSR and specific issues of environmental responsibility in the airline industry as the integrated model. Thus, we suggest an alternative perspective of CSR, which can apply exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…As environmental problems are increasingly recognised as persistent, global, and directly connected to a wide range of human stakeholders, businesses adopting stakeholder management initiatives will need to view the non-human stakeholder-the natural environment-as the most important organisational stakeholder. Strong collaboration amongst stakeholders is required going forward to achieve environmental sustainability [96,97]. Amongst all hotel stakeholders, hotels themselves and more so hotel chains are best placed to engage with and implement environmental sustainability policies and practices due to their organisational scale; specifically, their training and operational resources.…”
Section: Discussionmentioning
confidence: 99%
“…As environmental problems are increasingly recognised as persistent, global, and directly connected to a wide range of human stakeholders, businesses adopting stakeholder management initiatives will need to view the non-human stakeholder-the natural environment-as the most important organisational stakeholder. Strong collaboration amongst stakeholders is required going forward to achieve environmental sustainability [96,97]. Amongst all hotel stakeholders, hotels themselves and more so hotel chains are best placed to engage with and implement environmental sustainability policies and practices due to their organisational scale; specifically, their training and operational resources.…”
Section: Discussionmentioning
confidence: 99%
“…While applying (Yamane, 1967;Israel, 1992) with ±7% precision level where level of confidence is 95% and P = 0.5 thus, the sample for the study is 232 small and medium enterprises. The variables used in this study of corporate social responsibility are ethical, legal, philanthropic, economic (Carroll, 1991), and environmental responsibilities (Lee et al, 2019). Similarly, the variable of firm reputation is quality of employee, customer orientation or focus, quality of management (Schwaiger, 2004), and firm performance are product and service quality, customer retention, effectiveness (Spillan & Parnell, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Strong CSR contributes to the creation of a friendly environment that has a good impact. Lee et al, (2019) examined the impact of CSR image in the context of airline services by deploying the SEM and OLS techniques they found that CSR image develops with the experience and sharing of this experience allow the management to evaluate the CSR practices. A positive response towards the customers' experience sharing builds up the strong CSR image which ultimately invites customer satisfaction.…”
Section: Hypothesis Development Csr Image and Customer Satisfactionmentioning
confidence: 99%